Evaluation of metal aerosols in four communities adjacent to metal recyclers in Houston, Texas, USA. (3rd May 2020) - Han, Inkyu; Richner, Donald; An Han, Heyreoun; Hopkins, Loren; James, Daisy; Symanski, Elaine
ABSTRACT: The metal recycling industry provides jobs, generates revenue in local communities and conserves energy and resources. Nonetheless, possible negative impacts of metal recyclers (MRs) include the potential for emissions of metal aerosols and other dusts, noise, traffic and fire during operations. In Houston, Texas, there were more than 180 resident complaints about air quality related to MRs from 2006 to 2011 that were reported to the city's 311 call system. As a part of a community-based participatory research study, Metal Air Pollution Partnership Solutions (MAPPS), we evaluated the impact of metal emissions from MRs on air quality over two years in four environmental justice communities. We simultaneously collected samples of inhalable particles (aerodynamic particle size less than 10 µm, PM10 ) using a sampling strategy to capture emissions from the MRs while they were in operation at four locations within each community: an upwind location, the fence line of MR and two downwind locations and analyzed the samples for 10 metals. The highest values of iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), arsenic (As) and chromium (Cr) were detected at the fence lines of MRs. The normalized ratios of these metals at near and far neighborhood locations were 0.01 to 0.64 and 0.01 to 0.34, respectively, as compared with the metals at the fence line. The concentrations of metals rapidly decreased by 57–70% within 100 meters and reached similar levels at upwind (background) locations at approximately 600 meters. After adjusting the measured data for wind direction, rain and operating hours, we calculated non-carcinogenic hazard index values and carcinogenic risks for adult residents from breathing metals emitted from the facilities. Estimated inhalation cancer risks ranged from 0.12 case to 24 cases in 1 million people and the hazard index values ranged from 0.04 to 11. Implications : In Houston, Texas, residents complained about air quality related to metal recyclers from 2006 to 2011. Using a community-based participatory research method, metal emissions were characterized at four environmental justice communities. The results indicate that metal concentrations were the highest at the fence line and decreased by 57–70% within 100 meters and reached similar levels of background at 600 meters. After adjusting the measured data for meteorological parameters and operating hours, estimated inhalation cancer risks ranged from 0.12 cases to 24 cases in 1 million people and hazard index values ranged from 0.04 to 11.